Regional citrate anticoagulation in membrane based plasma exchange: Safety, efficacy and effect on calcium balance. Issue 8 (29th July 2018) - Christiadi, Daniel; Mercado, Chari; Singer, Richard
Abstract: Aim: To assess the efficacy, safety and calcium balance of a membrane based regional citrate anticoagulation plasma exchange protocol. Methods: This was an observational, prospective, single centre study of membrane separation plasma exchange using regional citrate anticoagulation. It was performed using a fixed dose pre‐filter citrate infusion that was based on the plasma flow rate. Patients received a post filter calcium infusion that was modified during treatment based on systemic ionized calcium monitoring. Post filter ionized calcium was not assessed. Safety and efficacy were assessed by extraction of clinical events and laboratory data contemporaneously recorded in electronic health records. Results: Thirty‐six sessions in five patients were performed. No patients developed symptomatic hypocalcaemia, and no patient had a recorded ionized calcium below 0.81 mmol/L. Filter clotting occurred in two sessions. The mean net calcium gained was 9.6 ± 1.8 mmol per session. Conclusion: Regional citrate anticoagulated membrane separation plasma exchange can be performed safely and effectively without the need for post filter ionized calcium monitoring. The algorithm employed resulted in a net calcium gain. Summary at a glance: Regional citrate is commonly used as an anticoagulant for dialysis in the Acute Kidney Injury (AKI) setting. This paper explores the use of regional citrate anticoagulation specifically for membrane‐based plasma exchange.